The Reality to Islamic Behavior and The Quality of Human Resources Performance at The Zakat Fund in Lebanon - Dar Al Fatwa - Souad Mahdi; Nurazmallail Marni (USIM Press, 2024)
Vol. 33 No. 1 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences [April 2021]